ANALYSIS OF THE HOSPITALIZATION COST AND THE APPROPRIATENESS OF ANTIBIOTIC USE OF TYPHOID FEVER IN GENERAL HOSPITAL IN YOGYAKARTA - Ria Etikasari; Tri Murti Andayani; Ali Gufron Mukti (Faculty of Pharmacy, Universitas Gadjah Mada)
The appropriate choosing of antibiotics to treat typhoid fever will effectively decrease the cost of care. The objectives of this study was to describe typhoid fever theraphy, the appropriate choosing of antibiotic, the total hospitalization cost of typhoid fever and the appropriateness between the Jamkesmas patient’s cost of hospitalization and the Indonesian Case Base Group’s (INA CBGs). The research was descriptive analytical research. The data were obtained through medical records of typhoid fever patients who were hospitalized in General Hospital of Yogyakarta from 1st October, 2009 up to 31st September, 2011. Patient’s were also observed to analized the use of antibiotics, while the patiens invoices were also analyzed to calculate the total hospitalization cost of typhoid fever. The statistical analisys that were used to analyzed the total cost of hospitalization in order to know the factor that influence that cost were the T-Test, Oneway Anova and Kruskal Wallis with the confidence level of 95%. Moreover, the one sample T-test was also used to compare the cost of hospitalization and the lenght of stay. The result of this research showed that 50 out of 86 of the total respondents were male. The age of that respondents were mostly 6-12 years old accounts for 35%. The majority of respondents were also categorized as general patient (41.86%) and 60.47% of the respondents were hospitalized in third class room. Moreover , most of the respondents were hospitalized for 5-10 days. The appropriateness of antibiotics use in child-age patients was 91.86% while in adults patient was 100%. The average of total cost of typhoid fever care for VIP room patients was IDR. 3,076,700.78 while for Askes patients the cost was IDR. 2,698,632.20. Factors that influence the cost of care were age (P = .013), lenght of stay (P = .001), class of service (P = .000), and kinds of medical service (P = .002). The total cost of care and lenght of stay of Jamkesmas patients agreed with the INA CBGs. Keywords: cost analysis, typhoid fever, antibiotic, INA CBGs